Present and future of breast cancer anti-Her-2-therapy - V. P. Letyagin (Опухоли женской репродуктивной системы, 2014)
The paper describes a new class of molecular targeted antitumor agents against the molecules involved in carcinogenesis. It considers the basic drugs of this class and their combinations and evaluates the efficiency of their use in therapy for breast cancer.